Integrated learning at primary schools in Lithuania - Tandzegolskienė-Bielaglovė, Ilona; Jakavonytė-Staškuvienė, Daiva; Kaminskienė, Lina (Pedagogika, 2023)
The research on integrated learning in primary grades in Lithuania was based on the curriculum spider web concept proposed by Akker (2003, 2010). In discussing successful experience of integrated curriculum design, development and implementation, researchers emphasize the balance between the main components of the curriculum: 1. The rationale or vision; 2. Goals and objects; 3. Content; 4. Educational activities; 5. Teacher's role; 6. Materials and resources; 7. Grouping; 8. Place; 9. Time; 10. Assessment. When evaluating the experience of implementing integrated curriculum at schools, all ten components should be addressed in a coherent way, to understand where the challenges and problems of implementing integrated curriculum exist, as well as to identify the strengths of schools’ practices and to anticipate where changes and improvements are needed. The research aim was to reveal attitudes of primary school teachers towards integrated curriculum and barriers to the implementation of integrated education in primary education. The study shows that a significant number of Lithuanian primary school teachers work in collaborative teams, and that educational practice is associated with the principle of fusion, which is developed at the school level through collaboration between practicing teachers, administrators, and researchers. Such areas as character education, citizenship, cooperation, communication, creativity, critical thinking, and skills are integrated into the curriculum. The lack of teaching materials for the organization of integrated curriculum (especially in the case of multidisciplinary activity sets) poses a particular challenge for primary school teachers, which requires a significant increase in the amount of time for preparing learning activities. The results of the study show that teachers express concern that, if integrated learning dominates the subject-based curriculum, students will achieve lower academic results in national standardized tests. Practice of integrated learning in other countries shows that when students receive targeted individual support, and when they participate in peer learning with a systemic teacher guidance, they develop both their social skills and critical, creative thinking through project-based or experimental activities. This makes students more motivated, eager to learn in a positive learning environment, and they perform significantly better on tests and show better individual progress.